The impact of product quality, service quality, price and location on satisfaction and behavioural intentions in housing industry:the moderating role of delivery systems / Aziam Mustafa - Mustafa, Aziam (Institute of Graduate Studies, UiTM, 2015)
Customer satisfaction is essential for enhancement of competitive advantage in housing industry. Customer satisfaction brings about a lot of positive implications to the companies, which may contribute to a successful business. It is essential to maintain the customers’ satisfaction by offering the right product and services that fulfill their needs and expectations. The customer satisfaction and behavioural intentions were studied and comparisons were made between two types of delivery systems; Sell Then Build (STB) and Build Then Sell (BTS) on the relationship between service providers’ attributes, satisfaction and behavioural intentions in housing industry. The service providers’ attributes are comprised of the product quality, service quality, price and location which refer to the aggregate services provided by the service provider to their buyers. The objectives of this study are threefold: (1) to examine the direct effect of service providers’ attributes comprises product quality, service quality, price and location on buyer’s satisfaction and behavioural intentions. (2) to examine the role of satisfaction as a mediating variable between product quality, service quality, price and location towards behavioural intentions and (3) to identify the moderating effect of the delivery systems (Sell Then Build and Build Then Sell) on the underlying relationship between product quality, service quality, price and location on buyers’ satisfaction and behavioural intentions…